PENILAIAN RISIKO GANGGUAN MUSCULOSKELETAL DISORDER PEKERJA BATIK DENGAN MENGGUNAKAN METODE STRAIN INDEX - Restuputri, Dian Palupi (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
Workers in batik industry in Indonesia are very big. The process of batik potentially causes interference in the musculoskeletal system (MSDs). This study aims to analyze employee complaints. Methods using Nordic Body Map questionnaires and work risk analysis on hand with Strain Index of batik workers. The result of the research shows that the workers' complaints are upper neck pain and 100% waist pain, upper arm, and back pain are 87.5%, and pain in the lower part of the neck, left shoulder, right shoulder, upper arm right and right hand is 75%. Based on the risk of work with the strain index method obtained results on Manual Pattern Drawing Posture, Posture Drawing Pattern With Ruler, Posture Batik Pattern, Coloring Posture Batik, Posture Coloring Batik Cap and Posture Washing both right hand and left hand classified the work observed dangerous.